The Relationship Between Outing Class Activities and Socio-Emotional Development in Early Childhood - Isnaini Isnaini; Lesis Andre; Sunimaryanti; Widia Siska; Ayu Mustika Sari; Resty Anggraini (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Social-emotional development in early childhood is crucial for building interpersonal skills and emotional regulation. However, classroom activities often do not provide sufficient opportunities for children to effectively develop social skills. This study aims to explore the impact of outing class activities on the social-emotional development of early childhood children at TK IT Sakinah Sungai Rumbai. A qualitative approach was used with direct observations and interviews with teachers and the principal. The findings show that outing class activities have a positive impact on the development of self-awareness, responsibility, and prosocial behavior in children. Children showed improvement in emotion regulation, conflict resolution, and peer interactions. Although some negative emotions, such as impatience and conflicts, were observed, these activities provided opportunities for children to learn how to manage these challenges. This study recommends that outing class activities be an integral part of early childhood education curricula to support comprehensive social-emotional development.